HEPATITIS B VACCINATION STATUS AMONG A TARGET GROUP BORN IN 1992-2000: A STUDY FROM BULGARIA - Aneliya Gotseva; Desislava Velcheva; Emilia Naseva (Peytchinski Publishing, 2024)
ABSTRACT: The purpose of this study is to determine the prevalence of stress among students of various health Hepatitis B virus (HBV) infection is a significant cause of morbidity and mortality and a leading cause of chronic liver disease. Vaccination has a key role in hepatitis B prevention. Compulsory immunization for all healthy newborns was introduced in Bulgaria in 1992 as part of the WHO global strategy. Purpose: The aim of this study was to determine the extent of post-vaccination seroprotection among persons born in 1992 - 2000 who received recombinant hepatitis B vaccine. Material/methods: A total of 923 serum samples of a target group of vaccinated individuals (412 males and 511 females) at a mean age of 23.0±2.7 years were tested over a two-year period (2018-2019). The quantitative analysis of hepatitis B surface antibodies (anti-HBs) levels was performed by CLIA using a LIAISON® anti-HBs II quantitative diagnostic kit (Dia Sorin, Italy). Results: All 923 individuals included in the study were hepatitis B surface antigen (HBsAg) negative. Protective anti-HBs titers ranging from 11 to >1000 mIU/mL were found in 45.3% of them. The sex distribution of the tested subjects varied significantly between years (p=0.023). The difference in protective anti-HBs levels between the two sexes was non-significant (p>0.05). There was a weak negative correlation between year of birth and anti-HBs titer (Pearson's r=0.351, p<0.001). Conclusions: The results of this large study conducted among subjects immunized against hepatitis B in childhood showed varying levels of post-vaccination seroprotection. On average, 23 years after universal immunization, 54.7% of the study cohort had no protective levels of anti-HBs (negative or equivocal result).